Conditions for Implementing Trolleybuses in Public Urban Transport - Zavada, Josip; Blašković Zavada, Jasna; Miloš, Katica (Promet - Traffic&Transportation, 2012)
Big cities in the world are burdened by heavy traffic and all the resulting negative consequences. A partial solution of this problem is achieved by the introduction of high-quality public urban transport of passengers that enables faster and more efficient transport. Since the introduction of individual forms of public urban transport depends on several factors, such as economic, traffic, environmental and technical ones, the problem is often a very complex one. The implementation of trolleybuses represents one of the forms of passenger transportation in public urban transport. It is the most favourable electrical vehicle for public urban transport when the implementation of a rail system is not affordable. Looking through history, the trolleybus has experienced significant changes in the implementation, in a large number of world urban environments. This paper points out the unjustifiable neglect of trolleybus in the implementation for the public urban transport and the renewed increase in the interest for its implementation. The advantages and drawbacks of the trolleybus are listed in relation to buses, as well as the reasons due to which some cities in the world are introducing it or increasing its implementation. The paper also emphasises and provides arguments of the ecological and energy advantages of trolleybuses in relation to buses as crucial in advanced public urban transport of passengers. Also, advanced technical solutions are pointed out that contribute to safer, faster and more comfortable transport of passengers. KEY WORDS: trolleybus, bus, public urban transport, environment, economics